Kearifan Lokal Dalam Prasasti Kawali: Implikasi Untuk Pendidikan Multikultural di Indonesia - Rahayu, Ratih (Universitas Tabanan, 2024)
This study examines the local wisdom embedded in the Kawali Inscription and its implications for multicultural education in Indonesia. Employing content analysis and a hermeneutic approach, the research reveals cultural values and life philosophies of ancient Sundanese society recorded in the inscription. The findings indicate that the Kawali Inscription contains moral teachings, social ethics, and leadership principles relevant to contemporary contexts. Furthermore, these local wisdom values have significant potential to enrich multicultural education curricula in Indonesia, particularly in fostering attitudes of tolerance, mutual respect, and cultural diversity awareness. The study concludes that integrating local wisdom into multicultural education can strengthen national identity while cultivating appreciation for the archipelago's cultural heritage.